2022
DOI: 10.1101/2022.11.17.22282418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CT perfusion stroke lesion threshold calibration between deconvolution algorithms

Abstract: Objective: CTP is an important diagnostic tool in managing patients with acute ischemic stroke, but challenges persist in the reliability of stroke lesion volumes determined with different software. We investigated a systematic method to calibrate CTP lesion thresholds between deconvolution algorithms using a digital perfusion phantom. Approach: The accuracy of one model-independent and two model-based deconvolution algorithms in estimating ground truth cerebral blood flow (CBF) and Tmax in the phantom was qua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Reader studies evaluating the potential benefit of mCTA-P maps in detecting ischemia and occlusions will be the subject of a future study. The optimal ischemic core threshold for our software was CBF < 15% for CTP 14 and CBF < 25% for mCTA-P ("Supplemental Materials") and not CBF < 30% as with RAPID CTP (RapidAI, Menlo Park, CA) used in clinical trials. Optimal stroke lesion thresholds vary by CTP software 14,37,38 and appropriate thresholds must accordingly be applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reader studies evaluating the potential benefit of mCTA-P maps in detecting ischemia and occlusions will be the subject of a future study. The optimal ischemic core threshold for our software was CBF < 15% for CTP 14 and CBF < 25% for mCTA-P ("Supplemental Materials") and not CBF < 30% as with RAPID CTP (RapidAI, Menlo Park, CA) used in clinical trials. Optimal stroke lesion thresholds vary by CTP software 14,37,38 and appropriate thresholds must accordingly be applied.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal ischemic core threshold for our software was CBF < 15% for CTP 14 and CBF < 25% for mCTA-P ("Supplemental Materials") and not CBF < 30% as with RAPID CTP (RapidAI, Menlo Park, CA) used in clinical trials. Optimal stroke lesion thresholds vary by CTP software 14,37,38 and appropriate thresholds must accordingly be applied. We also found that stroke lesion thresholds for mCTA-P was different to those of CTP due to the 4-image protocol ("Supplemental Materials"), which used substantially fewer images compared to a standard CTP protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations